Energy to Design Communities. Energy Communities and Communities of Practice to Support Marginal Areas in Abruzzo - Rossana Gaddi; Raffaella Massacesi; Luciana Mastrolonardo; Davide Stefano (Pad)
This contribution reports on an ongoing analytical experiment aimed at establishing a Renewable Energy Community in Taranta Peligna (CH), a highly marginalised municipality in the Italian Abruzzo region. The aim is to activate a Community of Practice to support local artisanal resources of high quality for the enhancement of energy and productive resources and thus to counteract the worrying depopulation that is taking place. With a systemic multi-objective approach to research, it is planned to define a distributed and collaborative model based on proximity, where the Municipality, with the participation of the community and the patronage of the Maiella Park Authority, can guide the creation of Energy Communities to obtain environmental, social, and economic benefits. In this perspective, a feasibility study based on an open-access geographic information system will provide an overview of the current energy situation, recovering the industrial and environmental heritage to define clean energy design scenarios, overcome energy poverty, generate economic improvements, and promote social awareness. Thanks to the holistic lever of systemic design, the proposed model faces difficulties in overcoming the classical economic approach and the deeply rooted individual culture, designing inclusive community-centered scenarios for social, cultural, economic, and, not least, energetic innovation. However, the research can only benefit from a local production model within the Maiella National Park, a UNESCO Geopark since 2021, rich in clean energy and authentic communities, witness of a strong manufacturing and industrial history characterized by excellence and authenticity.